2008
DOI: 10.1007/s10584-008-9418-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent and projected increases in atmospheric carbon dioxide and the potential impacts on growth and alkaloid production in wild poppy (Papaver setigerum DC.)

Abstract: In the current study, we quantified changes in the growth and alkaloid content of wild poppy, (Papaver setigerum) as a function of recent and projected changes in global atmospheric carbon dioxide concentration, [CO 2 ]. The experimental [CO 2 ] values (300, 400, 500 and 600μmol mol −1 ) correspond roughly to the concentrations that existed during the middle of the twentieth century, the current concentration, and near and long-term projections for the current century (2050 and 2090), respectively. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Similarly, elevated CO 2 resulted in increased alkaloids by altering the C/N balance toward a positive effect on biosynthesis of these metabolites [ 70 ]. Under elevated CO 2 , high levels of morphine, codeine, papaverine, and noscapine were produced in wild poppy ( Papaver setigerum ) [ 71 ], and scopolamine was accumulated in jimson weed ( Datura stramonium L.) [ 72 ]. In this study, we observed increased alkaloid biosynthetic pathway intermediates in both GCs and MCs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, elevated CO 2 resulted in increased alkaloids by altering the C/N balance toward a positive effect on biosynthesis of these metabolites [ 70 ]. Under elevated CO 2 , high levels of morphine, codeine, papaverine, and noscapine were produced in wild poppy ( Papaver setigerum ) [ 71 ], and scopolamine was accumulated in jimson weed ( Datura stramonium L.) [ 72 ]. In this study, we observed increased alkaloid biosynthetic pathway intermediates in both GCs and MCs.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, elevated CO 2 resulted in increased alkaloids, possibly by interfering with the C/N balance, and thus could have a positive effect on commercial-scale production of these metabolites. Under elevated CO 2 , significantly more morphine, codeine, papaverine and noscapine were produced in wild poppy (Papaver setigerum) (Ziska et al 2008), and higher levels of scopolamine were accumulated in jimson weed (Datura stramonium L.) than under ambient CO 2 (Ziska et al 2005). Due to the stimulatory effect of CO 2 , the amounts of specialized metabolites increased in several plant species (Ziska et al 2005).…”
Section: Elevated Co 2 Affects Plant Secondary Metabolismmentioning
confidence: 99%
“…The major consensus is that plant secondary metabolites increase with higher CO 2 levels (Schonhof et al 2007, Ziska et al 2008, Ghasemzadeh & Jaafar 2011, Ibrahim & Jaafar 2011. Since most known algal toxins, including domoic acid, saxitoxins, brevitoxins, and karlotoxins, are classified as secondary metabolites, it should not be entirely surprising that increased CO 2 levels can result in higher toxin cell quotas.…”
Section: Future Directionsmentioning
confidence: 99%